Wound healing potential of copper (II) bis [n'- (5-chloro-1hindol-3-yl) methyl nicotinic hydrazide] on experimentally induced excision wounds in rats / Morvarid Rahnama - Rahnama, Morvarid (2013)
Considering the importance of wounds in human health proclaims the necessity of discovering and developing new effective drug-to-be agents. Cl-indole-nicotinic is a Schiff base compound with promising structural potentials in accelerating healing of wounds. The purpose of present study is to investigate Cl-indole-nicotinic effects on wound healing and acute toxicity on Sprague Dawley rats as well as its activity as an antimicrobial and an antioxidant agent. The manually induced dermal incision on dorsal neck area of four groups of male SD rats were treated for 10 days with high dose compound (50 mg/kg), low dose compound (25 mg/kg), CMC 5%, and Intrasite gel to assess the medical nature of the compound. The superoxide dismutase (SOD) and malondialdehyde (MDA) tests signified the enzymatic antioxidant properties and level of lipid peroxidation (LP) in tissue homogenates prepared after removing the treated wound area. The acute toxicity effect of Cl-indole-nicotinic was characterized by monitoring six groups of male and female SD rats (low dose: 0.5g/kg, high dose: 1g/kg, and control: 10% Tween-20 groups) for two weeks after oral administration of the compound. Histological examination of kidney and liver, and verifying biochemical parameters of blood serum were done following sacrificing rats on day 14. In vitro evaluation of antioxidant potential of the compound is clarified by DPPH and FRAP tests. Antimicrobial activity of Cl-indole-nicotinic was determined against selected gram positive and gram negative bacteria based on disk diffusion method and results affirm compound’s inefficiency regarding the case. The minimum inhibitory concentration (MIC) of the compound is also distinguished. The outcomes from wound repair experience declared acceptable healing nature of the compound that was higher than Intrasite gel and increasing level of SOD along with compound’s concentration. Histological examination on rats’ inner organs showed no symptom of malignancy, which was considering the compound as non-toxic. Results affirm compound’s inefficiency regarding antibacterial activity but expressing in vitro antioxidant potency of the compound in some extent. Since the obtained results showed positive effects in different levels in most of selected tests in this study, Cl-indole-nicotinic could be presumed as a potential factor especially in case of healing wounds which offers the need of more knowledge and research about copper (II) Schiff bases as bioactive agents.